(untitled) (Journal of Universal Science Research, 2025)
Diversification of a variety of agricultural crops on moderately saline land helps to increase the productivity of agricultural products, which significantly increases the income of farmers. To date, due to the development of environmental and economic situations, issues of the production potential of various environmentally specialized plants are studied based on the adaptive strategy, the formation of the natural environment and the use of environmental optimization functions. All this requires constant attention to the environmental situation in the region and scientifically based measures aimed at maintaining and increasing the natural potential and fertility of the soil cover.